THE ROLE OF EXCHANGE IN CUSTOMER LOYALTY OF SOCIAL NETWORK SITES - Anandya, Dudi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2012)
Exchange has been known as the subject matter of Marketing. In this decade, Internet has enabled people to connect and exchange information to others, regardless of time and space. This condition leads to a new phenomenon, known as social networking through social network sites. In social network sites members find new kinds of exchange, which is information exchange. Memberships in many social network sites are free, which means that everyone is free to join or leave it. In that case social network providers must ensure that members keep using their site. The aim of this study is to test and analyze the direct and indirect effect of exchange to loyalty. The Unit of analysis in this study were members of social networking sites Friendster and Facebook. There are 256 respondents participate in this research. The result shows if community members keep exchange activity, they will loyal to the community. Direct effect has greater impact on loyalty than indirect effect. This means that social network company must encourage their member to exchange information actively.